Sensory Integration, Description Features and the Treatment - Avetisyan, Mariana (Զանգակ հրատ.)
The article describes the problem of "sensory integration", the need to study it, the peculiarities of its manifestation. Attempts are being made to draw professionals' attention to a problem that is often encountered today but is not evaluated or corrected accordingly in either children or adults. The problem is especially acute among schoolchildren. Our observations have shown that this problem may be at the root of negative educational motivation, failure to complete the curriculum, and bad behaviour. In other words, the child has an age-appropriate intellect, educated parents but exhibits bad behaviour or does not manage to educational programs. The work describes the possible signs that occur during sensory integration, as well as the case with the mentioned problem, the direction of the work aimed at overcoming it.
Keywords: Psychology